A8.18 Visfatin/PBEF in Bone Remodelling of Rheumatoid Arthritis. (25th February 2013) - Krumbholz, G; Junker, S; Lehr, A; Rickert, M; Schett, G; Lange, U; Rehart, S; Müller-Ladner, U; Neumann, E
Abstract : Objectives: Rheumatoid arthritis (RA) is associated with increased production of the adipocytokine visfatin in synovial fluid and tissue of RA patients. Visfatin promotes the synthesis of pro-inflammatory and matrix-degrading effector molecules in RA synovial fibroblasts. Moreover, an immunohistochemical analysis of RA bone tissue showed a co-localisation of visfatin with key cells of bone remodelling (osteoblasts, osteoclasts) but the role of this adipokine in processes of bone remodelling in RA is unclear. In this study, we focussed on visfatin and its influence on RA osteoblast and osteoclast activity and differentiation as well as on its immunomodulatory properties. Methods: Human osteoblasts and osteoclasts were isolated from bone tissue and blood samples of RA patients and stimulated with visfatin. Visfatin-mediated effects on osteoblasts and osteoclasts were analysed on the transcriptional and translational level using realtime polymerase chain reaction and immunoassays. Additionally, effects of visfatin on matrix-production of osteoblasts as well as differentiation and resorption activity of osteoclasts were examined by Alizarin-Red S-, TRAP- and von Kossa-staining. Results: Stimulation with visfatin induced the secretion of pro-inflammatory cytokines ( e.g. IL-6: 5-fold increase; IL-8: up to 100-fold) in RA osteoblasts. Additionally, quantitative realtime PCR showed several genes being differentially expressed in osteoblasts after stimulation with visfatin ( e.g . alkaline phosphatase, OPG, Osterix). In contrast, osteoclasts only weakly respond to visfatin. A regulation on translational level was observed with regard to the production of the cytokines IL-6 and IL-8, showing a moderate increase. Conclusions: The results of the present study indicate that visfatin influences the activity as well as the differentiation of human osteoblasts in RA by modulating the expression of genes being involved in matrix production and osteoblast phenotype development. These results support the idea of visfatin affecting bone metabolism in RA. Furthermore, the finding of cytokine-induction in osteoblasts and osteoclasts in RA confirm the pro-inflammatory potential of visfatin in RA. Acknowledgement: Funded by the German Research Society (SPP1468, IMMUNOBONE, NE1174/6–1).